Photograph of Leisure Hour participants (Raton, New Mexico Raton Range)
Photograph of the Leisure Hour participants after summer hiatus in the Raton Range
1 Lamenated Newspaper photograph.of the Leisure Hour participants
Master list item #22
File location is in the Raton File Cabinet drawer 3
Keywords: Library. -- Raton, New Mexico; Leisure hour participants -- Raton, New Mexico; Photograph -- Raton, New Mexico